(untitled) (Revista Direito em Debate, 2022)
This research analyzes the new ways of work through digital apps, in particular the one from the plataforma Ifood, in the contexto of the Fourth Industrial Revolution. Grounded on the dialectical-materialist method and the indirect documental research technique in the documental and bibliographic modality, the four Industrial Revolutions were analyzed and the work brokered by digital apps. The main goal was to examinate this types of labor, your consequences and verify the existence of subordination as the main point of caracterization of the employment bond. As major results, the study concluded that the work brokered by digital apps can create precariousness on the relations of labor and that the new theories about subordination are capable of demonstrate the existence of this requirement on the employment bond in the relationship between workers and companies, what evidence for the existence of employment bond.